STUDY OF NONLINEAR PROGRAM MODELS FOR SOLVING REVENUE MANAGEMENT IN AIRLINE TNDUSTRY - Siti Rusdiana et al. (Proceedings of ICMSA, 2005)
It is a common practice for Airline Industries have bargaining discountprices of tickets are sold to seat in cabin on the same flight. That callsRevenue Management. The yield management has focused mainly on theairline industries. Bathia, Parekh and Richter have developed some simpledecision rules to determine optimal booking limits in nested fare inventorysystem. To maximize the expected revenue, management needs todetermine the optimal times to switch between prices based on theremaining season and inventory.Keyword: Mathematical modeling, Nonlinear programming, InventoryControl